2003
DOI: 10.1038/nmat960
|View full text |Cite|
|
Sign up to set email alerts
|

ATP-independent contractile proteins from plants

Abstract: Emerging technologies are creating increasing interest in smart materials that may serve as actuators in micro- and nanodevices. Mechanically active polymers currently studied include a variety of materials. ATP-driven motor proteins, the actuators of living cells, possess promising characteristics, but their dependence on strictly defined chemical environments can be disadvantagous. Natural proteins that deform reversibly by entropic mechanisms might serve as models for artificial contractile polypeptides wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
225
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(235 citation statements)
references
References 24 publications
7
225
0
Order By: Relevance
“…1c) [Knoblauch et al, 2003]. This anisotropic response results in a decrease of aspect ratio from 10 to 3 and a more than threefold volume increase, which is the geometric basis for sieve tube plugging.…”
Section: Forisome Contraction In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…1c) [Knoblauch et al, 2003]. This anisotropic response results in a decrease of aspect ratio from 10 to 3 and a more than threefold volume increase, which is the geometric basis for sieve tube plugging.…”
Section: Forisome Contraction In Vitromentioning
confidence: 99%
“…Some sessile ciliates control the effective length of their stalk by means of the Ca 2ϩ -mediated contractility of a unique structure, the spasmoneme [Mahadevan and Matsudaira, 2000]. We have discovered that protein bodies in the vascular system of leguminous plants function as reversible cellular stopcocks by performing Ca 2ϩ -regulated contraction and expansion, thus superficially resembling spasmonemes [Knoblauch et al, 2001[Knoblauch et al, , 2003]. Here we summarize current knowledge of these so-called forisomes and provide a working hypothesis of their mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, it has frequently been hypothesized that the watery saliva interferes with the sieve plate occlusion mechanisms in response to penetration of the SE (16,20,23,24). One way that watery saliva could interfere with sieve plate occlusion would be to bind calcium in the SE and thus prevent calcium from exceeding a threshold level (25) that would trigger SE occlusion. Forisomes, one of the main components of SE occlusion in broad bean as described (12,13), are easy to extract and handle in vitro and are clearly visible under a light microscope (25).…”
mentioning
confidence: 99%
“…One way that watery saliva could interfere with sieve plate occlusion would be to bind calcium in the SE and thus prevent calcium from exceeding a threshold level (25) that would trigger SE occlusion. Forisomes, one of the main components of SE occlusion in broad bean as described (12,13), are easy to extract and handle in vitro and are clearly visible under a light microscope (25). Prior knowledge about the mechanism of forisome-based SE plugging and the ability to manipulate forisomes make broad bean an ideal model plant to visualize whether aphid saliva suppresses a rise in free calcium inside pierced SEs and hence sieve plate occlusion by secretion of watery saliva.…”
mentioning
confidence: 99%
“…They are thought to occlude the sieve pores in case of injury (Spanner, 1978). Light and confocal laser scanning microscopy studies have demonstrated that forisomes, crystalloid P-proteins found in Vicia faba and other faboid legumes, control the conductivity of sieve tubes (Knoblauch et al, 2001(Knoblauch et al, , 2003. The components of the forisomes have been identified and appear to be proteins unique to faboid legumes, although some of the motifs they contain have been identified in proteins from other plant taxa (Noll et al, 2007;Pelissier et al, 2008).…”
mentioning
confidence: 99%